Ritual matters: dynamic dimensions in practice - Brosius, Christiane; Hüsken, Ute (Taylor and Francis, 2012)
This book explores the interaction of rituals and ritualised practices utilising a cross-cultural approach. It discusses whether and why rituals are important today, and why they are possibly even more relevant than before.